The fat body in Rhinocricus padbergi (Diplopoda, Spirobolida) - Fontanetti, Carmem S. [UNESP]; Camargo-Mathias, Maria I. [UNESP]; Tiritan, Bianca M. S. [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2004)
The distribution and morphology of fat body of Brazilian diplopod Rhinocricus padbergi Verhoeff, 1938 are analyzed by scanning electron microscopy and histology. A terminology is proposed for description of the diplopods fat body.
Keywords: Fat body; diplopod; Rhinocricus; terminology